2005
DOI: 10.1021/cm050500x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Adsorbed Polystyrene and Poly(methyl methacrylate) Microspheres

Abstract: Monodisperse and spherical PS and PMMA microspheres, which are only conducting on the surface by the adsorption of carbon nanotubes, were used as the dispersed phase of electrorheological fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 58 publications
2
103
0
Order By: Relevance
“…When the PU was added to the nanotubes, the surfactant molecules could serve as a link between the nanotubes and polymers, providing hydrophobic interactions that can enhance the contact at the interface. [36] The stress-strain profiles for pure PU and PU/MWNTs composites are illustrated in Figure 11. The tensile strength and modulus were calculated from the stressstrain profiles and are shown in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…When the PU was added to the nanotubes, the surfactant molecules could serve as a link between the nanotubes and polymers, providing hydrophobic interactions that can enhance the contact at the interface. [36] The stress-strain profiles for pure PU and PU/MWNTs composites are illustrated in Figure 11. The tensile strength and modulus were calculated from the stressstrain profiles and are shown in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Table 2 showed that the element of P, N still remains in the final chars after combustion, indicating the excellent carbonization ability of PDSPB. Comparing other functionalized carbon nanotubes by organic substance such as PS [23] and PMMA [39] which are easy to burn out after combustion, the grafting of intumescent flame retardant (PDSPB) can improve dispersion and also flame retardancy. …”
Section: Flammabilitymentioning
confidence: 99%
“…[12][13][14][15] In the traditional ''graft to'' method, sonochemical treatment is used to introduce reactive sites on the SWNTs surface.…”
Section: Introductionmentioning
confidence: 99%